Developing And Evaluating ASMR-Based Digital Media To Enhance English Vocabulary Retention Among Indonesian High School Students: A Cognitive Approach - Ibad, Akhmad Irsadul; Maruf, Nirwanto; Kuchakovska, Halyna (Jurnal Pendidikan Progresif, 2025)
Developing and Evaluating ASMR-Based Digital Media to Enhance English Vocabulary Retention Among Indonesian High School Students: A Cognitive Approach. Objective: This study addresses the persistent challenge of English vocabulary retention among Indonesian high school students. Traditional rote memorization techniques remain inadequate in promoting long-term recall because they limit cognitive and sensory engagement. To overcome this issue, this research aimed to develop and evaluate an Autonomous Sensory Meridian Response (ASMR)-based digital media that leverages both cognitive and affective mechanisms to enhance vocabulary learning. Grounded in Cognitive Load Theory and Dual Coding Theory, the study sought to design an interactive platform that stimulates multisensory engagement, fosters focus, and reduces learning anxiety. Methods: A Research and Development (R&D) design, guided by the ADDIE model, was implemented with 90 Indonesian students from various public high schools in East Java. The study employed a mixed-methods approach involving pre-test and post-test vocabulary assessments, Likert-scale questionnaires on learner engagement, and semi-structured interviews. Quantitative data were analyzed using paired-sample t-tests and descriptive statistics, while qualitative data underwent thematic analysis to explore students’ experiences and perceptions. Findings: The results revealed a significant improvement in learners’ vocabulary retention (t(89) = 4.56, p < .001). Results revealed a significant improvement in learners' vocabulary retention (t(89) = 4.56, p< .001) with a large effect size (Cohen’s d = 1.40), indicating strong practical significance. Students in the ASMR-based learning condition reported high levels of motivation, attention, and enjoyment throughout the sessions, reflecting the intervention’s positive impact on cognitive and emotional engagement. Thematic findings highlighted enhanced focus, emotional relaxation, and metacognitive awareness of recall. Students with lower initial proficiency exhibited the greatest gains, indicating the intervention’s inclusive potential. Conclusion: The study concludes that a theory-driven, ASMR-based medium appears to be an engaging and promising approach for improving vocabulary acquisition. Integrating multisensory, affectively positive content transforms vocabulary learning into an immersive and emotionally safe experience. These findings provide both theoretical and practical evidence supporting ASMR as an innovative, low-cost pedagogical tool that can enhance language learning in diverse and resource-limited educational contexts. Keywords: ASMR-Based digital media, vocabulary retention, cognitive approach, research and development (R&D), transform vocabulary instruction.